Overtaking behaviour in elite and sub-elite 1500m short track speed skaters - Al, M.; Konings, M. J.; de Jong, R.; Hettinga, F. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Pacing can be seen as a continuous decision-making process related to how and when to invest your energy (Smits et al, 2014). Previous studies explored pacing behaviour as well as tactical positioning in short track speed skating competitions, and indicated that tactical positioning in the final stages of the race was highly related to finishing position in 1500m races (Konings et al, 2016). As a next step in understanding pacing and tactics in head to head competition in short-track speed skating, the present study explored overtaking behaviour of elite and sub-elite short track speed skaters in 1500m races. Methods: Intermediate positional rankings of 1500m races (13,5 laps) were collected per lap from short track speed skating World Cups, European and World Championships over the seasons 11/12 until 14/15 (N=7157 individual races). Short track speed skaters with a top 10 World Cup ranking were classified as elite speed skaters (ELITE; N=35 athletes, 716 individual races), while short track speed skaters with a World Cup ranking between 20-30th place were classified as sub-elite short track speed skaters (SUB; N=34 athletes, 392 individual races). The mean number of overtakings, being overtaken and total changing of positions (sum of overtaking and being overtaken) were calculated using the intermediate positions. Differences between elite and sub-elite short track speed skaters in overtaking frequency per lap were determined using independent Ttests (P<0.05). Results: ELITE overtook their opponents less frequently in lap 1 compared to SUB (ELITE= 0.2±0.2; SUB= 0.4±0.2, P=0.001). In contrast, ELITE showed a higher number of overtakings in lap 10 (ELITE= 0.2±0.1; SUB=0.1±0.1, P<0.001) and lap 12 (ELITE= 0.2±0.1; SUB=0.1±0.1, P=0.002) compared to SUB. ELITE were overtaken more frequently than SUB in lap 1 (ELITE= 0.5±0.2; SUB= 0.4±0.2, P=0.004), but less frequently in lap 11 (ELITE= 0.1±0.1; SUB= 0.1±0.1, P<0.001), lap 12 (ELITE= 0.1±0.1; SUB= 0.1±0.1, P=0.046) and lap 13 (ELITE= 0.1±0.1; SUB= 0.1±0.1, P=0.022). Finally, no differences were found in the total changing of positions between ELITE and SUB. Conclusion: The present study showed that elite short track speed skaters distinguished themselves from sub-elite short track speed skaters by demonstrating on average both a higher number of overtakings as well as being overtaken less frequently by their opponents in the final, decisive part of the race.